Case Report: De novo KLHL24 Gene Pathogenic Variants in Chinese Twin Boys With Epidermolysis Bullosa Simplex - Xu, Xiaojing; Zhao, Juan; Wang, Chao; Qu, Xiaoxuan; Ran, Menglong; Ye, Fang; Shen, Ming; Wang, Kundi; Zhang, Qi (Frontiers in Genetics, 2021)
Objectives: The aim of this study was to determine the molecular etiology and clinical manifestations of a pair of Chinese twins affected with epidermolysis bullosa simplex. Pediatricians should pay attention to the early genetic diagnosis of this disease. Methods: Histopathological examination of HE-stained skin, electron microscopy of biopsied normal skin, and whole-exome sequencing was performed to assess pathogenicity and conservation of detected mutations. Two years later, the cutaneous and extracutaneous manifestations of the twins were comprehensively evaluated. Results: A de novo pathogenic variant c.2T>C (p.M1T) in KLHL24 (NM_017644) was identified in both twins. The characteristics of extensive skin defects on the extremities at birth and the tendency to lesson with increasing age were confirmed. No positive sensitive markers, such as B-type natriuretic peptide, cardiac troponin I, for cardiac dysfunction were detected. Conclusions: The de novo pathogenic variants c.2T>C (p.M1T) in KLHL24 (NM_017644) contributes to the development of epidermolysis bullosa. Genetic diagnosis at birth or early infancy can better predict the disease prognosis and guide the treatment.